2020
DOI: 10.1051/e3sconf/202016706005
|View full text |Cite
|
Sign up to set email alerts
|

A framework of penta-helix model to improve the sustainable competitiveness of the wine industry in Baja California based on innovative natural resource management

Abstract: This paper presents an innovative natural resource management framework for the wine industry based on the Penta-Helix Model and Open Innovation features. As an initial activity, a particular survey was designed in order to be applied to a lot of companies to determine the necessities perception related to the elements of sustainable competitiveness. In fact, the evaluation of sustainable competitiveness is the key to the innovate framework proposed. Considering the results related to the elements of sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
1
7
0
2
Order By: Relevance
“…Pentahelix has been carried out in previous studies as a problem-solving [1] found that Pentahelix has five actors namely Government, Private, Society, Media, and Academics. This is in line with [2] and [3]. Pentahelix continues to be studied and used in case management.…”
Section: Introductionsupporting
confidence: 82%
“…Pentahelix has been carried out in previous studies as a problem-solving [1] found that Pentahelix has five actors namely Government, Private, Society, Media, and Academics. This is in line with [2] and [3]. Pentahelix continues to be studied and used in case management.…”
Section: Introductionsupporting
confidence: 82%
“…Memberdayakan masyarakat Pulau Tunda ini bisa dijadikan pengembangan sumber daya manusia di pulau tersebut sehingga pelatihan edutourism sehingga keaktifan dari bidang kepariwisataan dapat diwujudkan dengan adanya pembuatan suatu perencanaan perencanaan yang maksimal dengan perhatian terhadap keanekaragaman, kekhasan yang dimiliki Pulau Tunda. Dimana dalam penentuan pengembangan strategi di sektor pariwisata bisa dilakukan dengan penggunaan pentha helix models, dengan penerapan model tersebut telah diatur dalam Peraturan Menteri Pariwisata Republik Indonesia Nomor 14 Tahun 2016 tentang Pedoman Destinasi Pariwisata Berkelanjutan sehingga dengan pelatihan eduturism ini penggunaan pentahelix sangat dibutuhkan sebagai pendorong untuk meningkatkan peranan di bidang government, community, academic, business, and media electronict (Cabrera-Flores et al, 2020;Chamidah et al, 2021;Syafari, 2018;Yasir et al, 2021). Dengan adanya penerapan pentahelix dalam pelatihan edutourism ini bisa meningkatkan kerjasama lintas sektor dalam peningkatan perekonomian di wilayah pesisir yang berbasiskan pada pengetahuan sehingga dapat meningkatkan kemampuan masyarakat dalam berinovasi dan berwirausaha melalui kegiatan kolaborasi (Calzada, 2019(Calzada, , 2020.…”
Section: Pendahuluanunclassified
“…Their dynamic participation allows them to benefit from tourism activities and indirectly enhance their community values and livelihood. The such effect would only come from active stakeholder deliberation and consensus, noting its impact on the community, based on a healthy environment and ecology principles, and in line with the local's values in social, culture, tradition, and religion (Cabrera-Flores et al, 2020). However, besides different geographical locations, the livelihood assets' impact may differ from that faced by the local community due to the internal and external stakeholders' support.…”
Section: Penta-helix Tourism Development Strategymentioning
confidence: 99%
“…They also planned to develop tourism and environmentally friendly management patterns (Nainggolan et al, 2020). Hence, the government must adapt to determine the best innovative activities to endorse governance arrangements linked to transparency, all-inclusiveness, equality, lawfulness, incorporation, competence, and responsibility in tourism development (Cabrera-Flores et al, 2020;Ikhtiagung & Radyanto, 2020).…”
Section: Governmentmentioning
confidence: 99%